2001
DOI: 10.1074/jbc.m105434200
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Thr-353 of the Conserved Phosphorylation Loop of the Sarcoplasmic Reticulum Ca2+-ATPase in MgATP Binding and Catalytic Activity

Abstract: Mutants in which Thr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 43 publications
2
34
0
1
Order By: Relevance
“…The present study expands on our previous studies of domain P mutations, which investigated the role of the conserved phosphorylation loop 351 DKTGTLT in MgATP binding (6,7). We now focus on the other conserved segments of the P domain mentioned above.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The present study expands on our previous studies of domain P mutations, which investigated the role of the conserved phosphorylation loop 351 DKTGTLT in MgATP binding (6,7). We now focus on the other conserved segments of the P domain mentioned above.…”
mentioning
confidence: 51%
“…The reaction was started by the addition of ATP to the Ca 2ϩ -bound Ca 2ϩ -ATPase. Other phosphorylation and dephosphorylation experiments were carried out by manual mixing techniques (7). Acid quenching was performed with 0.5-2 volumes of 25% (w/v) trichloroacetic acid containing 100 mM H 3 PO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Closure of the cleft between N-and P-domain is thought to occur to bring ATP close to Asp 351 upon nucleotide binding (20,21). In line with that, mutations at Asp 351 , Lys 352 (25), and Thr 353 (26) alter the affinity of ATP to the ATPase.…”
mentioning
confidence: 79%
“…If an interaction between nucleotide and ATPase had only local effects on the protein structure, a weakened interaction would selectively reduce the amplitude of difference bands associated with that conformational change, but not of all of the bands as observed here. Particularly interesting is that functional groups of ATP, which interact with different domains of the protein, produce the same type of conformational change: the amino function is thought to interact with the N-domain (19,24,46) and the ␥-phosphate with the P-domain (25,26,46). Despite that, the absence of the ␥-phosphate in ADP (28) or of the adenine amino group in ITP both reduce the amplitude of the same bands.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies of purified enzyme in aqueous solution support this interpretation (3)(4)(5)(6)(7). However, a study in an organic solventwater mixture concluded that the true substrate is Mg⅐P i (8), and recently the equation for the half-maximum Mg⅐P i concentration was used to interpret an increased half-maximum P i concentration when the upstream threonine in a signature amino acid sequence for P-type pumps (DKTGT) was changed to serine (9). The interpretation given to most studies of Na,KATPase is also that Mg 2ϩ and P i bind randomly (10 -12).…”
mentioning
confidence: 99%